2018
DOI: 10.3390/su11010177
|View full text |Cite
|
Sign up to set email alerts
|

The Segmentation of Polish One-Person Households Due to Consumption

Abstract: The scientific objective of the study was to identify consumption patterns in one-person households, living independently. The households’ clusters were emerged using Ward’s grouping method. It can be concluded that distinguishing the consumption patterns for one-person households is possible on the basis of diversifying both level and structure of incomes as well as socio-demographic differences between them. Depending on economic and socio-demographic variables, disparate consumption patterns for these types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the United Kingdom, distributed system operators who conducted the ‘Low Carbon London’ project, used the electricity consumption profiles of 5567 households to cluster these households into distinct social groups 29,30 . Other works from 31,32 also supports the idea of using sociodemographic to distinguish between households.…”
Section: Introductionmentioning
confidence: 96%
“…In the United Kingdom, distributed system operators who conducted the ‘Low Carbon London’ project, used the electricity consumption profiles of 5567 households to cluster these households into distinct social groups 29,30 . Other works from 31,32 also supports the idea of using sociodemographic to distinguish between households.…”
Section: Introductionmentioning
confidence: 96%
“…This represents 28% of all U.S. households in 2021, whereas only 13% of all US households in 1960 were SPHs. This growing trend has been attributed to changes in demographic behaviors, institutional arrangements, and labor migration in the past few decades [ 4 ]. Other hypothesized economic and sociocultural variables influencing the rise in SPHs include individualism, late marriages, low birth rates, and an elderly population, as well as employment opportunities for women [ 5 , 6 ] this makes the SPH a very diverse group [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that single-member households have different characteristics from multi-member households. Single-member households are thought to be successful people, and they are considered to be sophisticated consumers and a group that values independence in their lives [11]. Moreover, single-member households tend to pursue convenience in food consumption and preparation to a greater extent than multimember households [11].…”
Section: Introductionmentioning
confidence: 99%
“…Single-member households are thought to be successful people, and they are considered to be sophisticated consumers and a group that values independence in their lives [11]. Moreover, single-member households tend to pursue convenience in food consumption and preparation to a greater extent than multimember households [11]. As such, due to the distinctive characteristics of single-member households compared to multi-member households, various industries are developing products and services for them.…”
Section: Introductionmentioning
confidence: 99%